2002
DOI: 10.1007/s005920200014
|View full text |Cite
|
Sign up to set email alerts
|

Acrochordon and impaired carbohydrate metabolism

Abstract: Acrochordons were reported to have a probable association with diabetes mellitus but detailed data about this relation has not been introduced yet. We evaluated 120 patients with acrochordon for the presence of impaired carbohydrate metabolism. Overt diabetes mellitus (DM) was found in 88 patients and glucose intolerance was detected in 6 patients; 4 patients had reactive hypoglycemia. We concluded that acrochordons may be skin markers of underlying impaired carbohydrate metabolism and the patients with acroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
5
9

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 4 publications
7
50
5
9
Order By: Relevance
“…This was in concordance with the study by Demir et al 8 . In our study 78.6% of patients with acrochordons had a total cholesterol more than 200 and the association was statistically significant (p=0.032) and was in concordance with the study by Shah et al in Indian population 9 .…”
Section: Periorbital Miscellaneous Disorderssupporting
confidence: 94%
“…This was in concordance with the study by Demir et al 8 . In our study 78.6% of patients with acrochordons had a total cholesterol more than 200 and the association was statistically significant (p=0.032) and was in concordance with the study by Shah et al in Indian population 9 .…”
Section: Periorbital Miscellaneous Disorderssupporting
confidence: 94%
“…The study done by Omar et al showed that the prevalence of Skin tags were more among diabetic patients. 5 Similarly, study of Demir et al 7 showed that patients with skin tags were found to have overt DM. They found diabetes in 73.3% of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Molluskum pendulum lezyonları olan hastalarda DM ve obezite varlı-ğının araştırıldığı çalışmalarında Koçak ve arkadaşları 17 hastaların %35,1'inde BKİ değerinin 30'un üstünde olduğunu saptamış ve kan şekeri yüksekliğini %37,8 oranında bildirmişlerdir. Demir ve arkadaşla-rı 18 120 hastanın 88'inde DM, 6'sında bozulmuş glukoz tolerans testi saptamışlardır. Aynı çalışmada hastalarda molluskum pendulum varlığı ile karbonhidrat metabolizması bozukluğu arasında ilişki olduğu düşü-nülmüş, lezyon sayısının BKİ değeri yüksek olan kişilerde daha fazla olduğu belirtilmiştir.…”
Section: Discussionunclassified